Chinese philosophy in an era of globalization - Wang, Robin (Albany : State University of New York Press, 2004)
Annotation This book treats Chinese philosophy today as a global project, presenting the work of both Chinese and Western philosophers. Providing contemporary considerations of the Chinese philosophical tradition and bringing Chinese philosophy into conversation with Western philosophy, "Chinese Philosophy in an Era of Globalization provides a model for collaborative work. Topics covered include value theory, philosophy of religion, human nature, virtue ethics, epistemology, and philosophy of language.
Axiology in pre-modern Chinese philosophy / Zhang Dainian ; translated by Eric L. Hutton -- On the idea of axiology in pre-modern Chinese philosophy / Kwong-loi Shun -- The Chinese path to polytheism / Zhao Dunhua ; translated by Miranda D. Brown -- Monotheism in the philosophy of religion: a response to Professor Zhao / Stephen T. Davis -- The discussion of mind and nature in Zhu Xi's philosophy / Chen Lai ; translated by Robert W. Foster -- What is living and what is dead in the Confucianism of Zhu Xi? / Bryan W. Van Norden -- Contrasting Confucian virtue ethics and MacIntyre's Aristotelian virtue theory / Wan Junren ; translated by Edward Slingerland -- Once more on Confucian and Aristotelian conceptions of the virtues: a response to Professor Wan / Alasdair MacIntyre -- The polished mirror: reflections on natural knowledge of the way in Zhuangzi and Alvin Plantinga / Kelly James Clark and Liu Zongkun -- Reflections on "The Polished Mirror" / Alvin Plantinga -- Heidegger's view of language and the Lao-Zhuang view of Dao-language / Zhang Xianglong ; translated by Stephen C. Angle -- Speech from beyond the reach of language: a response to Zhang Xianglong / Merold Westphal.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Philosophy, Chinese; Philosophy, Modern -- 20th century; Philosophy, Modern; Philosophie chinoise; Philosophie -- 20e siècle.; PHILOSOPHY -- Eastern; Philosophy, Chinese; Philosophy, Modern; 1900-1999